Forecasting using econometric approach (e-powtimesanalysis) / Norafefah Mohamad Sobri ...[et al.] - Mohamad Sobr, Norafefah; Abd Malik, Mohd Azry; Wan Husin, Wan Zakiyatussariroh; Che Yusof, Nur Syaliza Hanim; Ismai, Idari (2018)
The objective of this study is to develop interactive learning multimedia of Powerpoint (POWTOON) in teaching and learning activities especially in reading subject. The study also aims to examine the effectiveness of power point in forecasting approach especially in econometric chapter. A total of 39 students from part 4 Diploma in Statistics , UiTM Cawangan Kelantan were selected as sample. The interactive learning multimedia of time series analysis course was successfully developed and named as 'e-powtimesanalysis'. This 'e-powtimesanalysis' gives significant and valuable contributions to statistics educational practice and knowledge in the area of time series anaysis in the context of Malaysian Institution of Higher Learning. The findings also reveals that the students performance improved by 15.69% when teaching and learning process integrated the interactive approach. The implication of this study suggested that the 'e-powtimesanalysis' can be used to enhance the quality of teaching and learning process in statistics education and simultanoeusly increase the students' performance in times series and forecasting subject